Functional characterisation of small RNAs in Acinetobacter baumannii using Hi-GRIL-seq - Hamrock, Fergal James (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2021)
Acinetobacter baumannii is a priority pathogen that is a leading source of nosocomial multidrug resistant (MDR) infections worldwide. A key to the success of A. baumannii is the ability to quickly adapt to changing environmental conditions by regulating gene expression programmes which includes genes that are important antimicrobial resistance (AMR), environmental persistence and virulence. This study examines how an MDR strain of A. baumannii is capable of persisting in adverse conditions using posttranscriptional regulatory mechanisms. Understanding these mechanisms will inform future research into how this organism causes disease and how it has evolved into an MDR opportunistic pathogen. To identify the posttranscriptional regulatory mechanisms that promote bacterial survival, we experimentally identified mRNA targets of candidate regulatory sRNAs by employing the proximity ligation procedure Hi-GRIL-seq that ligates RNA-RNA interaction pairs into chimeric molecules independently of RNA chaperones. The sRNA-containing chimeras were identified and mapped to the A. baumannii genome to identify mRNA targets. Hi-GRIL-seq procedure was performed during growth in rich medium and following iron starvation and exposure to antibiotics to identify potential targets regulated under such conditions. Filtering Hi-GRIL-seq generated chimeras based on abundance identified the most likely targets for each sRNA, which led to the identification of over 1500 potential sRNA-mRNA interactions many of which are expected to play essential roles in virulence, metabolism, iron responses and AMR. Eight sRNA-mRNA interaction partners were selected for further mechanistic investigation by analysing ligation junctures of the chimeras for these interaction partners and predicting their duplex structures. By integrating the Hi-GRIL-seq output with bioinformatic sRNA-target mRNA predictions tools CopraRNA and TargetRNA2, we identified 16S rRNA pseudouridine synthetase as target for regulation by sRNA21. The identified sRNA-mRNA interactions were experimentally tested by using a previously established two-plasmid approach. This system uses a translational fusion of GFP with the target RNA as a reporter of sRNA-based posttranscriptional regulation. By measuring the GFP abundance in E. coli co-expressing the sRNA and the cognate target mRNA-GFP compared to controls, we confirmed two sRNA-mRNA interaction. The sRNA21 suppresses the expression of 16S rRNA pseudouridine synthase and sRNA97 enhances the expression of an alpha-keto acid decarboxylase family protein. Recent evidence suggests that these targets may be involved in regulating persistence and amino acid metabolism. This study demonstrates the power Hi-GRIL-seq can play in elucidating novel sRNA-mRNA interactions. The combination of this procedure with computational predictions and experimental validation promises to enable description of the entire A. baumannii targetome.
APPROVED